2020
DOI: 10.13106/jafeb.2020.vol7.no6.109
|View full text |Cite
|
Sign up to set email alerts
|

Nexus between Indian Economic Growth and Financial Development: A Non-Linear ARDL Approach

Abstract: The study examines the nexus between financial development and economic growth in India during Q1: 1996 to Q3: 2018. This study employs time-series data of real GDP and ratio of broad money to GDP as a proxy for economic and financial development, respectively. The data are obtained from RBI database on the Indian economy. All variables are seasonally adjusted using X12-arima technique and expressed in natural logarithm form. Non-linear Autoregressive Distributed Lag (NARDL) bound test has been used to check f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 21 publications
0
21
0
2
Order By: Relevance
“…However, the proposition of linear relationship between financial development and economic growth is restrictive, especially when policy intervention occurs in the economy (Ibrahim, 2015). Recent empirical literature highlighted the importance of non-linear relationships between financial development and economic growth (Deidda & Fattouh, 2002;Kumar & Paramanik, 2020;Rahman, Khan, & Charfeddine, 2020). However, empirical research on non-linear relationship between financial development and economic growth with respect to Pakistan is scant.…”
Section: Introductionmentioning
confidence: 99%
“…However, the proposition of linear relationship between financial development and economic growth is restrictive, especially when policy intervention occurs in the economy (Ibrahim, 2015). Recent empirical literature highlighted the importance of non-linear relationships between financial development and economic growth (Deidda & Fattouh, 2002;Kumar & Paramanik, 2020;Rahman, Khan, & Charfeddine, 2020). However, empirical research on non-linear relationship between financial development and economic growth with respect to Pakistan is scant.…”
Section: Introductionmentioning
confidence: 99%
“…Through the partial total decomposition process, a basic variable can be separated into both positive and negative components to analyze dynamic and nonlinear asymmetry. Using the NARDL model, recent studies have found evidence of asymmetric exchange rate effects on stock prices (Ajayi & Mougouė, 1996;Bahmani-Oskooee & Saha, 2015, 2016Cheah et al, 2017;Cuestas & Tang, 2017;Kumar & Paramanik, 2020) According to the author's knowledge, studies of the same topic in Vietnam have not mentioned the potential non-linear dynamic relationship between exchange rates and stock prices. That makes the research results unconfirmed (affirmed) the existence of a close long-run relationship between the variables.…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study inferred that labor productivity as well as sectoral contribution have favorable effects on growth, welfare and household income of Nepal. Kumar and Paramanik (2020) showed that economic growth rate is affected positively by financial development in the long run, while Luong, Nguyen, and Nguyen (2020) revealed that economic growth indicators have negative and statistically significant impact on the shadow economy. Moreover, Ngo, Cao, Nguyen, and Nguyen (2020) highlighted that FDI is affected by size of market and Nurlanova, Omarov, and Satpayeva (2020) identified that innovative activities is most important factor affecting sustainable development…”
Section: Literature Reviewmentioning
confidence: 99%